MENANGKAL ISU AGAMA MENGGUNAKAN PERSPEKTIF MODERASI BERAGAMA DALAM MENINGKATKAN PARTISIPASI POLITIK PADA PEMILIHAN UMUM 2019 - agam zuama agam; arthur rachman; abdul wahid (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2023)
This study aims to explain the politicization and religious issues used in the 2019 General Election as a form of political participation in relation to religious moderation. This research uses qualitative research methods, namely by collecting accurate data about elections that have been passed by the community. In this discussion it is explained how religion becomes a full force in nominating pairs of candidates in elections from religious groups. The theory used in this study uses the theory of political participation of Michael Rush and Philip Althoff. Identity politics is also very pronounced in elections because couples who run in 2019 have interests that carry the interests of religious groups in Indonesia. Similarly, various religious groups and organizations that adorn political life have led to the assumption that the 2019 election can generate good participation politically and look at the 2024 elections which will later have many candidates competing in the Presidential and Vice President exchanges. However, its relationship with religion is so close that it will cause visible effects felt by the community. Kata Kunci : Agama, Pemilu, Moderasi Beragama